Inclusion of physical activity in nurse practitioner programs: A national perspective. Issue 5 (21st May 2022) - Falcon, Ashley; Vermeesch, Amber; Stoutenberg, Mark; Sampson, Emma; Bender-Stephanski, Meg; Webb, Willow; Woo, Yerin
ABSTRACT: Background: Physical activity (PA) provides a multitude of health benefits, creating an avenue for disease prevention and management. Health care providers play a crucial role in helping patients become more active, yet little is known about the preparation of primary care nurse practitioners (NPs) to aid in this effort. Purpose: To examine the amount and type of PA training offered in primary care NP programs in the United States. Methodology: A cross-sectional study design was used. Eligible programs' websites were reviewed, and an online survey of program leaders assessed details regarding the inclusion of PA training, barriers, and future plans. Results: Data extracted from 1, 067 NP program websites revealed that 81.7% of websites ( n = 264) with course descriptions contained one or more general health promotion keywords, whereas only 0.6% ( n = 2) included a PA-specific keyword. Two-hundred institutions (53.2%) completed the program leader survey, of which 45.0% reported no inclusion of PA training. Among institutions providing PA training, 82.2% ( n = 88) and 55.1% ( n = 59) reported the inclusion of aerobic activity and strength training recommendations, respectively. Forty-one institutions (46.1%) felt that their institution prepared students to effectively counsel patients on starting a PA program. Conclusions: Although some NP programs include PA content, most provide no or less-than-adequate PA training. Implications for practice: The current state of PA training in NP programs may hinder health promotion and disease prevention efforts. Programs should dedicate sufficient time and attention to preparing future NPs to promote PA behaviors. A multifaceted, multistakeholder approach is needed to facilitate widespread adoption of PA inclusion.